Przyczyny niepowodzenia negocjacji rolnych w ramach bieżącej rundy rokowań na forum Światowej Organizacji Handlu - Rygalski, Mieczysław (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2003)
Nearly ten years have now passed since the conclusion of the Uruguay Round negotiations. This paper makes an attempt to provide some partial answers to the question how agricultural policies have responded to the international framework of rules and commitments during this period. Main conclusion is that levels of support provided to agricultural producers in OECD countries have not declined significantly until the present round. While the UR Agreement on Agriculture forces developing countries to cut tariffs, which are in many cases their only means of protecting agriculture, there are numerous possibilities that allow rich countries to continue subsidizing their own farmers, enabling them to dump products on the world market at less than the cost of production. The fifth Ministerial Conference held in Cancun in the frame of the present round of WTO negotiations ended abruptly without consensus on any of the items on its agenda. The collapse of Cancun is another big signal that it is time for introspection of the world order on the role that international institutions must play to guard against the abuse of power of a few and make the benefits of world trade fully accessible to all, notably those in the developing countries.